Avaliação da contaminação do fluido de preservação de órgãos e do enxerto em transplantes renais - Soares, Diogo Peres Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Introduction: Contamination of preservation solution (PS) in solid organ transplants is relatively underexplored in the literature, and its true impact on postoperative morbidity and mortality in transplants is therefore not well understood. In this study, we characterized the incidence of PF contamination in grafts from kidneys obtained from deceased donors at a leading transplant center. Objective: To evaluate and characterize the contamination rate of the PS and kidney graft from deceased donors, originating from different organ procurement centers in the state of São Paulo, and to attempt to establish a correlation with donor characteristics and the postoperative outcomes of the recipients. Patients and Methods: All kidneys consecutively sent to the Kidney Transplant Center at Hospital das Clínicas of Botucatu Medical School - UNESP, between January 2018 and May 2022, originating from various procurement centers, were retrospectively evaluated. The sampling of the material sent for culture was performed under strict surgical asepsis principles, where approximately 40 milliliters of the preservation solution that was in contact with the kidney and a fragment of perirenal fat were sent, in a sterile container, for analysis of bacterial and fungal contamination. The results obtained were cross-referenced with donor and recipient data, as well as the duration of cold storage. Results: Among the 360 organs evaluated, 59.72% (n = 215) came from male donors and 36.67% (n = 132) from female donors, with a median age of 41 years. Trauma was the leading cause of death in 42% of cases, followed by hemorrhagic stroke in 16%. Among the donors, 61% had no associated comorbidities; however, 25% were hypertensive, 11% were smokers, and 7% used some type of illicit drug. Exclusive renal harvesting occurred in 58% of cases (200 patients), with an ICU stay of 4 days. Documentation of at least one infectious site in the donor occurred in 87 patients (25%), with pulmonary infection responsible for 20% of cases. Approximately 81% of the organs offered for transplantation came from ideal donors, with a creatinine level at the time of procurement of 1.1 mg/dL and a cold ischemia time of 21 hours. Among the recipients, the median age at the time of surgery was 52 years, 60% were male, with an average body mass index of 26 kg/m². Before the transplant, 84% of the recipients had hemodialysis as their main renal replacement therapy, followed by peritoneal dialysis in 12%, with a pre-transplant dialysis duration of 35 months. Among the main causes of renal failure, renal failure of undetermined origin was observed in 30% of the cases, followed by diabetes in 24%, systemic arterial hypertension in 11%, and glomerulopathies in 6% of the cases. The overall contamination rate in the sampled material was 28.9%, with no statistically significant difference between the positivity in the PS and tissue fragment samples (17.5% versus 22%, respectively, p=0.134). The most common isolated organism in PS was Staphylococcus epidermidis (25.3% of the samples analyzed). Considering the high-risk germs, Staphylococcus aureus was the most prevalent (8.4%), followed by Escherichia coli, Klebsiella pneumoniae, Psedomonas sp (5.6%), Enterococcus faecalis, and Candida sp, present in 3.5% of the samples analyzed. The comparison of donor characteristics according to culture positivity did not demonstrate a statistically significant relationship, either with constitutional variables (sex, age, cause of death, presence of diabetes, etc.) or with those related to hospital stay (length of ICU stay, type of donation, cold ischemia time, or even the presence of prior donor infection). Likewise, the comparison of the main unfavorable outcomes associated with the recipient population who underwent RT did not demonstrate a statistically significant difference according to the positivity of the PS/tissue culture. Conclusion: Although the positivity of the cultures obtained from the PS samples was significant, it was not possible to establish a direct correlation between contamination and worse outcomes in the transplanted patients. Similarly, it was not possible to correlate the greater positivity of the cultures with the characteristics of the donor or recipient populations studied.

Introdução: A contaminação da solução de preservação (SP) em transplantes de órgãos sólidos é relativamente pouco discutida na literatura, sendo, pois, a sua real importância na morbimortalidade pósoperatória do transplante, pouco valorizada. Neste trabalho caracterizamos a incidência da contaminação do SP do enxerto em rins provenientes de doadores falecidos, em um serviço de referência em transplantes. Objetivo: Avaliar e caracterizar a taxa de contaminação da SP e do enxerto renal provenientes da captação a partir de doadores falecidos, oriundos dos diferentes centros de captação de órgãos no estado de São Paulo, tentando estabelecer uma correlação com as características do doador e com a evolução pós-operatória do receptor. Pacientes e métodos: Foram avaliados de maneira retrospectiva todos os rins encaminhados consecutivamente ao Centro de Transplante Renal do Hospital das Clinicas da Faculdade de Medicina de Botucatu – UNESP entre janeiro de 2018 e maio 2022, oriundos dos diferentes centros de captação. A amostragem do material encaminhado para cultura foi realizada obedecendo aos rígidos princípios de assepsia cirúrgica, onde cerca de 40 mililitros da solução de preservação que se encontrava em contato com o rim e um fragmento da gordura perirrenal foram enviadas, em frasco estéril, para análise de contaminação bacteriana e fúngica. Os resultados obtidos foram cruzados com os dados provenientes do doador e do receptor, além do tempo que o órgão permaneceu estocado em gelo. Resultado: Dentre os 360 órgãos avaliados, 60% (n=215) dos doadores eram do sexo masculino e 37% (n=132) do sexo feminino, com mediana de idade de 41 anos. O trauma foi a principal causa de óbito em 42% dos casos, seguido pelo acidente vascular cerebral hemorrágico, em 16%. Entre os doadores, 61% não apresentavam comorbidades associadas; 25% eram hipertensos, 11% tabagistas e 7% faziam uso de algum tipo de droga ilícita. A captação renal exclusiva ocorreu em 56% dos casos (200 pacientes), com um tempo de permanência em unidade de terapia intensiva (UTI) de 4 dias. A documentação de pelo menos um sítio infeccioso no doador ocorreu em 87 pacientes (24%), sendo o foco pulmonar responsável por 20% dos casos. Cerca de 81% dos órgãos ofertados para transplante eram provenientes de doadores ideais, com creatinina no momento da captação de 1,1mg/dL e tempo de isquemia fria de 21 horas. Entre os receptores observou se que a mediana da idade no momento da cirurgia foi de 52 anos, sendo que 60% eram do sexo masculino, com um índice de massa corpórea médio de 26kg/m2. Antes da realização do transplante, 84% dos receptores tinham como principal terapia renal substitutiva a hemodiálise, seguida pela diálise peritoneal em 12%; com tempo de diálise pré-transplante de 35 meses. Dentre as principais causas de perda da função renal, a insuficiência renal de causa indeterminada foi observada em 30% dos casos, seguida pelo diabetes com 24%, hipertensão arterial sistêmica em 11% e glomerulopatias em 6% dos casos. A taxa global de contaminação no material amostrado foi de 28,9%, sem diferença estatisticamente significante entre a positividade nas amostras da solução de perfusão e fragmento de tecido (17,5% versus 22%, respectivamente, p=0,134). A maioria dos organismos isolados na SP eram Staphylococcus epidermidis (25% das amostras analisadas). Considerando se os germes de alto risco, observamos que o Staphylococcus aureus foi o mais prevalente (8,4%), seguido pela Escherichia coli, Klebsiella pneumoniae e Psedomonas sp (5,6%) e, finalmente, Enterococcus faecalis e Candida sp, perfazendo 3,5% das amostras analisadas. A comparação das características do doador em função da positividade da cultura, não demonstrou relação estatisticamente significativa, seja com as variáveis constitucionais (sexo, idade, causa de óbito, presença de diabetes, etc.), seja com aquelas relacionadas à internação hospitalar (tempo de UTI, tipo de doação, tempo de isquemia fria ou mesmo a presença de infecção prévia do doador). Da mesma 18 forma, a comparação das principais variáveis evolutivas desfavoráveis associadas à população de receptores submetida a TR não demonstrou diferença estatisticamente significativa em função da positividade da SP. Conclusão: Embora a positividade das culturas obtidas a partir das amostras da SP tenha sido significativa, não foi possível estabelecer uma correlação direta entre a sua contaminação e uma pior evolução dos pacientes transplantados. Da mesma forma, não foi possível correlacionar a maior positividade das culturas com as características das populações de doadores ou de receptores estudadas.
Assessment of contamination in organ preservation fluid and grafts in kidney transplants
Keywords: Solução de preservação; Contaminação; Rim; Enxerto; Transplante